Crude oil price among 7 selected Asian countries / Arissa Athirah Abdul Jalil and Nadhirah Uzma Shaharudin - Abdul Jalil, Arissa Athirah; Shaharudin, Nadhirah Uzma (Faculty of Business and Management, 2019)
Crude oil is one of the important element in the global economics, especially the economy of developing countries. Therefore, there have been many studies to investigate the variables which affect crude oil price (OP). Considering some variables which have affected the oil price, this study tried to investigate the relationship between gross domestic product (GDP), stock market (SM), exchange rate (ER) and crude oil production (COP) with crude oil price among seven selected Asian countries which are Columbia, India, Indonesia, South Korea, Japan, Malaysia and Thailand by using the annual data from 2008 to 2017. To achieve the objectives of the study, regression fixed random model was used to assess the relationship between exchange rate (ER), stock market (SM), crude oil production (COP) and gross domestic product (GDP) with crude oil price (OP). The results of the study demonstrated that gross domestic product (GDP) and crude oil production have positive significant. On the other hand, exchange rate (ER) have negative significant and stock market (SM) have negative insignificant relationship with crude oil price (OP).